Exploration of photosensitive polyimide as the modification layer in thin film microcircuit. (February 2018) - Liu, Lily; Song, Changbin; Xue, Bin; Li, Jing; Wang, Junxi; Li, Jinmin
Abstract: Positive type photosensitive polyimide is used as the modification layer in the thin film transistors production process. The photosensitive polyimide is not only used as the second insulating layer, it can also be used instead of a mask because of the photosensitivity. A suitable curing condition can help photosensitive polyimide form the high performance polyimide with orderly texture inside, and the performance of imidization depends on the precise control of temperature, time, and heat control during the curing process. Therefore, experiments of different stepped up heating tests are made, and the ability of protecting silicon dioxide is analyzed.